A proof-of-concept study in small and large animal models for coupling liver normothermic machine perfusion with mesenchymal stromal cell bioreactors - Umberto Cillo; Caterina Lonati; Alessandra Bertacco; Lucrezia Magnini; Michele Battistin; Liver NMP Consortium; Lara Borsetto; Francesco Dazzi; David Al-Adra; Enrico Gringeri; Maria Laura Bacci; Andrea Schlegel; et al. (Nature Communications)
Abstract To fully harness mesenchymal-stromal-cells (MSCs)’ benefits during Normothermic Machine Perfusion (NMP), we developed an advanced NMP platform coupled with a MSC-bioreactor and investigated its bio-molecular effects and clinical feasibility using rat and porcine models. The study involved three work packages: 1) Development (n = 5): MSC-bioreactors were subjected to 4 h-liverless perfusion; 2) Rat model (n = 10): livers were perfused for 4 h on the MSC-bioreactor-circuit or with the standard platform; 3) Porcine model (n = 6): livers were perfused using a clinical device integrated with a MSC-bioreactor or in its standard setup. MSCs showed intact stem-core properties after liverless-NMP. Liver NMP induced specific, liver-tailored, changes in MSCs’ secretome. Rat livers exposed to bioreactor-based perfusion produced more bile, released less damage and pro-inflammatory biomarkers, and showed improved mithocondrial function than those subjected to standard NMP. MSC-bioreactor integration into a clinical device resulted in no machine failure and perfusion-related injury. This proof-of-concept study presents a novel MSC-based liver NMP platform that could reduce the deleterious effects of ischemia/reperfusion before transplantation.